Monitoring solar activity with PEPSI. Issue Volume 14:Issue A30(2018) (August 2018) - Dineva, Ekaterina; Denker, Carsten; Strassmeier, Klaus G.; Ilyin, Ilya; Pevtsov, Alexei A.
Abstract: Synoptic Sun-as-a-star observations are carried out with the Potsdam Echelle Polarimetric and Spectroscopic Instrument (PEPSI), which receives light from the Solar Disk-Integration (SDI) telescope. Daily spectra are produced with a high signal-to-noise ratio, providing access to unprecedented quasi-continuous, long-term, disk-integrated spectra of the Sun with high spectral and temporal resolution. We developed tools to monitor and study solar activity on different time-scales ranging from daily changes, over periods related to solar rotation, to annual and decadal trends. Strong chromospheric absorption lines, such as the Ca ii H & K λ3934 & 3968 Å lines, are powerful diagnostic tools for solar activity studies, since they trace the variations of the solar magnetic field. Other lines, such as Hα λ6563 Å line and the near-infrared (NIR) Ca ii λ8542 Å line, provide additional information on the physical properties in this highly complex and dynamic atmospheric layer. Currently, we work on a data pipeline for extraction, calibration, and analysis of the PEPSI/SDI data. We compare the SDI data with daily spectra from the Integrated Sunlight Spectrometer (ISS), which is part of the Synoptic Long-Term Investigation of the Sun (SOLIS) facility operated by the U.S. National Solar Observatory (NSO). This facilitates cross-calibration and validation of the SDI data.